2018
DOI: 10.1109/tcsvt.2017.2757063
|View full text |Cite
|
Sign up to set email alerts
|

Localized LRR on Grassmann Manifold: An Extrinsic View

Abstract: Subspace data representation has recently become a common practice in many computer vision tasks. It demands generalizing classical machine learning algorithms for subspace data. Low-Rank Representation (LRR) is one of the most successful models for clustering vectorial data according to their subspace structures. This paper explores the possibility of extending LRR for subspace data on Grassmann manifolds. Rather than directly embedding the Grassmann manifolds into the symmetric matrix space, an extrinsic vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…This paper discusses the possibility of extending the subspace data LRR on manifolds. Instead of embedding manifolds directly in symmetric matrix space, it establishes a local self-representation in the tangent space of each point, so as to obtain the local LRR method of manifolds, but there is still a lack of detailed explanation steps [1]. Taktaktak Kal-lel believes that the study compares the effects of positive feedback and negative feedback on students' dance learning.…”
Section: Introductionmentioning
confidence: 99%
“…This paper discusses the possibility of extending the subspace data LRR on manifolds. Instead of embedding manifolds directly in symmetric matrix space, it establishes a local self-representation in the tangent space of each point, so as to obtain the local LRR method of manifolds, but there is still a lack of detailed explanation steps [1]. Taktaktak Kal-lel believes that the study compares the effects of positive feedback and negative feedback on students' dance learning.…”
Section: Introductionmentioning
confidence: 99%
“…Table 5 summarized the performance of the proposed framework for Ballet dataset. Moreover, the comparison with the recent state-of-the-arts (Liu & Pei, 2014;Ming et al, 2014;Vishwakarma et al, 2016a;Wang, Hu, et al, 2017;Zhu & Xia, 2015) in also surpasess all the existing state-of-the-arts which utilized SDEG and R-Transform-based action descriptor (Vishwakarma et al, 2016), optical flow features (Liu & Pei, 2014;Zhu & Xia, 2015) to assimilate shape and temporal variation of action with SVM classifier. It is also identified that the concept of Multiple Instance Learning using Iterative Querying Heuristic algorithm (Zhu & Xia, 2015) instead of SVM resulted in better results…”
Section: Performance Comparison With State-of-the-artmentioning
confidence: 68%
“…Low-rank representation (LRR) has recently attracted considerable interest as its pleasing efficacy in exploring low-dimensional subspace structures embedded in data, which is very helpful for data clustering. However, in many computer vision applications, data often originate from a manifold, which is equipped with some Riemannian geometry, and the low-rank representation over the manifold [14,42,45] is required. This problem can be formulated as min…”
Section: Low-rank Representation Over the Manifoldmentioning
confidence: 99%